(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
All human beings are consumers. They consume things of daily use. They also consume and buy these products according to their needs, preferences and buying powers. Now, people are becoming more aware about good health and they are moving towards natural products and therapies, because they believe that the herbal or Ayurvedic products represent the protection in contrast to the artificial that are considered to be unsafe to the human and environment. On the other side, some people prefer Allopathic medicine system as they consider that these medicines gives quick relief and also easily available everywhere at any time. In India, drugs of herbal origin have been used in traditional systems of medicines such as Unani and Ayurveda since ancient times. In this study, an attempt has been made to study the customers satisfaction towards the usage of Ayurvedic products.